2005
DOI: 10.1089/ten.2005.11.319
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Three-Dimensional Cultures Significantly Increase Hematopoietic Differentiation Efficacy of Embryonic Stem Cells

Abstract: Stem cell-based tissue engineering is a promising technology in the effort to create functional tissues of choice. To establish an efficient approach for generating hematopoietic cell lineages directly from embryonic stem (ES) cells and to study the effects of three-dimensional (3D) biomaterials on ES cell differentiation, we cultured mouse ES cells on 3D, highly porous, biomimetic scaffolds. Cell differentiation was evaluated by microscopy and flow cytometry analysis with a variety of hematopoiesis- specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 53 publications
2
88
0
1
Order By: Relevance
“…Efficacy of HSPC generation was analyzed as reported before. 25 15,16 In addition, cells that express only c-Kit or only sca-1 were also analyzed to determine the unique profile of differentiated cells in each bioreactor culture.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy of HSPC generation was analyzed as reported before. 25 15,16 In addition, cells that express only c-Kit or only sca-1 were also analyzed to determine the unique profile of differentiated cells in each bioreactor culture.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…[22][23][24] Our laboratory has previously demonstrated that this type of bioreactor could significantly increase hematopoietic differentiation of cells cultured in scaffolds. 25 Similarly, the SyntheconÔ rotary cell culture system, a microgravity type bioreactor with a slowturning lateral vessel, originally developed by NASA, has also been reported to increase the efficiency of EB formation and differentiation of stem cells into the three germ layers of embryonic development. 26 Comparison of spinner flask and Synthecon bioreactors for human ES cell differentiation, specifically focusing on cardiac and endothelial lineages, has also been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, several groups have recently shown that mouse EBs can be formed directly from enzymatically dissociated mESCs in stirred reactors [19‱‱] or a rotary cell culturing system [20]. Mouse EBs can also be formed in stirred vessels by removing LIF from mESC aggregates produced in the same vessels [16‱‱] [22].…”
Section: Stem Cell Expansion and Differentiation In Bioreactorsmentioning
confidence: 99%
“…Cell behavior and phenotype have been shown to differ in 2D and 3D environments [22]. Although valuable insights into cell migration have been gained from 2D studies into cell movement, cells in vivo undergo morphogenesis and migrate in 3D.…”
Section: Biophotonicsmentioning
confidence: 99%